2022
DOI: 10.1002/hrm.22131
|View full text |Cite
|
Sign up to set email alerts
|

A social network perspective on workplace inclusion: The role of network closure, network centrality, and need for affiliation

Abstract: Organizations are increasingly recognizing the important role employee inclusion perceptions play in promoting positive employee attitudes and behaviors. Although social networks are frequently cited as being a driver of perceived inclusion, little empirical work has examined the social network conditions that give rise to it. We address this gap by examining how both network position (indegree centrality) and network structure (network closure) relate to perceived workplace inclusion. We test our hypotheses w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 76 publications
0
2
0
Order By: Relevance
“…Additionally, many studies have demonstrated the influence of gender on professional networking. 11 , 25 If the demographic information would have been available to connect to each Q-sort, hand rotation of the data could have been performed to determine quantitative differences based upon the participants’ work location or gender.…”
Section: Limitationsmentioning
confidence: 99%
“…Additionally, many studies have demonstrated the influence of gender on professional networking. 11 , 25 If the demographic information would have been available to connect to each Q-sort, hand rotation of the data could have been performed to determine quantitative differences based upon the participants’ work location or gender.…”
Section: Limitationsmentioning
confidence: 99%
“…Prior studies have examined the interaction of social network properties and personality characteristics in the formation of work outcomes (Van Knippenberg and Hirst, 2020). For example, recent studies found that the need for affiliation, an individual's desire for belongingness, and social connection to others (McClelland, 1985), can exert an influence on the consequences of an individual's social network structure (Grosser et al, 2022). Further, gender is a primary identity used in the categorization of the self and others in business contexts.…”
Section: Practical Implicationsmentioning
confidence: 99%